Students’ Legal Awareness of Personal Data Protection at AMIK Bukittinggi - Roslaili Roslaili (Civiliza Publishing, 2026)
The development of digital technology in higher education institutions has increased the use of academic information systems while also raising the risk of misuse of students’ personal data; therefore, legal awareness is needed to support the implementation of Law No. 27 of 2022 on Personal Data Protection. This study aims to analyze the level of students’ legal awareness regarding personal data protection at AMIK Bukittinggi. The study employed a quantitative approach with a descriptive design involving 76 students selected through total sampling. Data were collected using a Likert-scale questionnaire that measured four dimensions of legal awareness: knowledge, understanding, attitude, and legal behavior. The instrument was found to be valid and highly reliable (Cronbach’s Alpha = 0.894), while data analysis was conducted using descriptive statistics. The results indicate that students’ level of legal awareness falls into the high category with an average score of 76.76; 75.00% of respondents fell into the high and very high categories. All dimensions of legal awareness also fell into the high category, with the legal behavior dimension achieving the highest average score, while the legal attitude dimension had the lowest average score. These findings suggest that students possess a good level of legal awareness regarding the protection of personal data. This study provides an empirical contribution to the development of research on legal awareness and serves as a foundation for universities to strengthen policies and digital legal literacy programs to support the implementation of personal data protection.